Limited Predictive Utility of Admissions Scores and Objective Structured Clinical Examinations for APPE Performance - McLaughlin, Jacqueline E. (Am J Pharm Educ, 2015)
Objective. To examine the relationship between admissions, objective structured clinical examination (OSCE), and advanced pharmacy practice experience (APPE) scores. Methods. Admissions, OSCE, and APPE scores were collected for students who graduated from the doctor of pharmacy (PharmD) program in spring of 2012 and spring of 2013 (n=289). Pearson correlation was used to examine relationships between variables, and independent t test was used to compare mean scores between groups. Results. All relationships among admissions data (undergraduate grade point average, composite PCAT scores, and interview scores) and OSCE and APPE scores were weak, with the strongest association found between the final OSCE and ambulatory care APPEs. Students with low scores on the final OSCE performed lower than others on the acute care, ambulatory care, and community APPEs. Conclusion. This study highlights the complexities of assessing student development of noncognitive professional skills over the course of a curriculum.